A randomized, double blind, single dose, comparative study of the pharmacokinetics, safety and immunogenicity of MB02 (bevacizumab biosimilar) and reference bevacizumab in healthy male volunteers. Issue 3 (4th September 2021) - Sinn, Angela; García‐Alvarado, Fernanda; Gonzalez, Veronica; Huerga, Camino; Bullo, Felicitas
Abstract : Aims: The pharmacokinetic (PK) similarity between MB02, a proposed bevacizumab biosimilar, and reference bevacizumab approved from the USA (US‐bevacizumab) and European Union (EU‐bevacizumab) was evaluated. Safety and immunogenicity were also assessed. Methods: In this phase 1, randomized, double blind, single dose, parallel group study, 114 healthy male volunteers were randomized 1:1:1 to receive a 3 mg/kg intravenous dose of MB02, US‐bevacizumab or EU‐bevacizumab, and evaluated for 100 days. PK similarity between MB02 and reference bevacizumab was determined using the standard bioequivalence criteria (0.80–1.25) for the area under the serum concentration–time curve from time 0 extrapolated to infinity (AUC(0‐∞) ) and the maximum observed serum concentration (Cmax ). Results: Baseline demographics were similar across treatment groups. All study drugs exhibited similar PK profile. The 90% confidence interval for the geometric lead square means ratios for the primary parameters AUC(0‐∞) and Cmax for MB02, US‐bevacizumab and EU‐bevacizumab were fully contained within the pre‐defined bioequivalence limits for the 3 pairwise comparisons: AUC(0‐∞) (MB02:US‐bevacizumab 0.998 [0.944 to 1.05]; MB02:EU‐bevacizumab 1.07 [1.00 to 1.14]; and US‐bevacizumab:EU‐bevacizumab 0.934 [0.884 to 0.988]) and Cmax (MB02:US‐bevacizumab 0.983 [0.897 to 1.08]; MB02:EU‐bevacizumab 1.06 [0.976 to 1.16]; and; US‐bevacizumab: EU‐bevacizumab 0.926 [0.851 to 1.01]). Treatment emergent adverse events were reported in 87 subjects (76.3%), most being mild and with comparable incidence among treatment groups. Thirty‐three subjects (28.9%) reported 56 possibly related treatment emergent adverse events with comparable incidence across treatments, the most frequent being headache (10.5%) and fatigue (3.5%). Anti‐drug antibody incidence was low and similar between treatment groups. Conclusions: This study demonstrates the PK similarity and bioequivalence of MB02 to the reference bevacizumab, whether approved from USA or EU. The safety and immunogenicity profile of MB02 was shown also to be similar to the bevacizumab reference product (NCT 04238663).